Sectoral value added prices, TFP growth, and the low-skilled wage in high-income countries - Matthias Lücke (Kiel Institute of World Economics (IfW), 1999)
This econometric analysis investigates the impact of changes in sectoral valueadded prices and total factor productivity (TFP) on the equilibrium relative wage of low-skilled workers in eleven high-income countries. The key finding is that TFP growth mandated an increase in the unskilled wage, relative to the remuneration of human capital, during the 1970s, but a decrease during the 1980s. This is consistent with the observation that, in most sample countries, the relative wage and employment opportunities of low-skilled workers tended to improve until about 1980, but have deteriorated since then. While the regression results suggest that technological change played a large role in shifting labour demand against low-skilled workers, this conclusion is qualified because the empirical evidence is also compatible with product upgrading and outsourcing of low-skill intensive production activities to low-income countries.
Keywords: F16; O33; 330; Ungeschützte Beschäftigung; Lohnstruktur; Arbeitsnachfrage; Außenwirtschaft; Faktorproportionentheorem; Faktorpreisausgleich; Technischer Fortschritt; Produktivität; Humankapital; Mehr-Sektoren-Modell; Auslandsproduktion; Schätzung; OECD-Staaten